Importancia del diseño gráfico publicitario en el posicionamiento de las PYMES de Tungurahua - Sánchez Zapata, Jhonny Edison (2023)
With the arrival of COVI-19 and the economic crisis derived from it, SMEs were forced to take measures in this regard in order to safeguard their sustainability. One of these measures was to seek the sale and promotion of its products through digital channels, which developed a rapid growth of technology in the world. However, not all companies were able or used this type of strategy, especially companies from developing countries such as Ecuador. Therefore, the present work aims to determine the importance of graphic design in the positioning of SMEs located in the province of Tungurahua-Ecuador. Through the use of an inductive and deductive methodology, in addition to a mixed or better said qualitative and quantitative approach, the bibliographic and field method was used for the collection of information, where an observation sheet and the interview with the managers were applied. Of the 6 textile companies that made up the study sample, 6 employees of the companies were also randomly selected in order to apply a survey to them. The main results obtained were that a large part of the companies studied do not give significant importance to the use of graphic design since they consider it unprofitable; however, the companies that have continuously used this type of strategy presented higher brand recognition rates. to the competition. It was concluded that advertising graphic design is one of the main tools that brands can use to communicate and capture the attention of potential customers or consumers.